The Indonesian Throughflow and its Impact on Biogeochemistry in the Indonesian Seas - Edwards Taufiqurrahman; A’an J. Wahyudi; Yukio Masumoto (Universitas Gadjah Mada, 2020)
It has been widely known that the Indonesian Throughflow (ITF) is an important inter-ocean connection with unique and complex oceanographic and geographic conditions, as well as a strong relation to both regional and global ocean currents and climate systems. Many studies on characteristics, mechanisms, and impacts of the ITF have been conducted, mainly focusing on the ITF pathways, transport, water mass mixing processes, and their variability in connection with monsoons and climate systems. In this paper, we summarize some of the critical aspects related to ocean conditions within the Indonesian Seas and the Indonesian Throughflow, with the main focus on studies of marine biogeochemistry in a region affected by the ITF. Although the biogeochemical cycle is one of the key research topics that are needed to advance our ocean understanding, studies on marine biogeochemistry within the Indonesian Seas are quite limited due to less observed data compared to the physical parameters. Further studies on biogeochemistry and efforts to conduct in situ and remotely sensed observations in this region are strongly required. Here, we propose several biogeochemical observations correlated to the ITF.